Problem-Based Learning Virtual Comic Media Based on Cultural Diversity Material - I Dewa Agung Alit Pranata; Ida Bagus Gede Surya Abadi (Jurnal Edutech Undiksha, 2023)
The limited media owned by teachers to support the online learning process impacts learning that could be more optimal. In addition, the teacher gives assignments as the most dominant method in online learning. This development research aims to develop virtual comic media for IPS content on cultural diversity. This type of research is developed using the ADDIE model. The data collection method used in this study is a non-test method, with the instrument used in the form of questionnaires. The data analysis technique used is descriptive qualitative and quantitative analysis. The results of the research are media that are developed properly with the results of the review of subject content experts, design experts, and instructional media experts, the results of individual and small group trials successively obtaining a percentage score (91.6%), (100%), (98 .8%), (97.2%), and (95.3%). Based on the validation and trial results, the developed virtual comic learning media can be used as a learning medium for teaching social studies material in the context of cultural diversity material for class IV SD. Virtual comic learning media can help students in learning.